The Influence of Nature toward the Main Character’s Self-Realization in David Malouf’s An Imaginary Life: an Eco-Critical Reading - Faridz Al-Anshari; Marliza Yeni (English Department, Faculty of Humanities, Andalas University, 2019)
This article discusses David Malouf’s novel entitled An Imaginary Life from an eco-critical perspective. It examines certain symbols from nature that appear in the novel during the journey of Ovid, the main character, in the exile. The data is collected by applying library research methods. Primary data are all symbols from nature related to Ovid’s journey and the formation of his new identity in the exile. Meanwhile, the secondary data are all information from books and articles related with archetypal symbols and criticism. The result of analysis is presented by the descriptive method. The analysis results in two conclusions. Firstly, nature that is presented as wild at the beginning of the story turns into a home for the main character at the end of the story. Secondly, nature, represented by some symbols, evidently plays an important role in making Ovid embrace his new life and forms new identity apart from his past life as a famous poet back in Rome.